(untitled) (Bangladesh Journal of Anatomy, 2011)
Context: Arm span is the most reliable body parameter for predicting the stature of an individual.It is useful in predicting age related loss in stature and in identifying individuals with disproportionate growth abnormalities and skeletal dysplasias. Since in Bangladesh variegated ethnic groups inhabit in different climatic, nutritional and ecological conditions, no single anthropometric formula is suitable. The present study was undertaken to measure the stature, as well as arm-span and to determine whether there is any correlation between the stature and the arm-span. And to estimate using respective multiplication factors the stature from arm span and to assess the effectiveness of the above estimation by comparing the ‘estimated’ values with the ‘measured’ values. Study Design : Cross sectional descriptive type of study. Materials and Method: The study was carried out with a total number of 100 Christian Garo adult female aged between 25 to 45 years. Arm-span along with their stature was measured directly from the subjects by using anthropometric technique by a measuring tape. The data were then statistically analyzed by computation to find out its normative value. Multiplication factors were estimated for estimating stature and comparison were made between measured and estimated stature using paired "t" test. Result : The mean normal values of the arm-span is 154.74 (±5.69) cm and the stature 152.79 (±5.62) cm were found. The multiplication factor was estimated for the same hand measurements with the stature. Significant positive correlation was found in case of arm-span with the stature (r =0.89). Key words: Anthropology; Correlation; Multiplication factor; Stature DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8139 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 5-9